2021
DOI: 10.1038/s41388-021-01656-1
|View full text |Cite
|
Sign up to set email alerts
|

LIMK1 promotes peritoneal metastasis of gastric cancer and is a therapeutic target

Abstract: Peritoneal metastasis is a common form of metastasis among advanced gastric cancer patients. In this study, we reported the identification of LIM domain kinase 1 (LIMK1) as a promoter of gastric cancer peritoneal metastasis, and its potential to be a therapeutic target of dabrafenib (DAB). Using transcriptomic sequencing of paired gastric cancer peritoneal metastasis, primary tumors, and normal gastric tissues, we first unveiled that LIMK1 is selectively up-regulated in metastatic tumors. Increased LIMK1 in ga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 43 publications
2
24
0
Order By: Relevance
“…Gene expression was calculated as fragments per kilobase of transcript per million mapped reads) by DESeq2. 9 Statistical analysis Data are presented as mean±SD. Differences between two groups were compared using Student's t-test.…”
Section: Rna Sequencingmentioning
confidence: 99%
“…Gene expression was calculated as fragments per kilobase of transcript per million mapped reads) by DESeq2. 9 Statistical analysis Data are presented as mean±SD. Differences between two groups were compared using Student's t-test.…”
Section: Rna Sequencingmentioning
confidence: 99%
“…LIM domain kinase (LIMK) is a class of serine/threonine protein kinases (3); previous studies indicated that LIMK1 was highly expressed in numerous malignant tumors and correlated with patients' poor prognoses (4)(5)(6)(7)(8). However, there is little research on the role of LIMK2 in malignant tumors.…”
Section: Introductionmentioning
confidence: 99%
“…Evidence showed that PM is one of the most frequent types of metastasis in GC and up to 14% of newly diagnosed GC patients ( Kang et al, 2021 ). Furthermore, the peritoneum is considered the most common site of recurrence upon radical surgery in GC patients ( Sugarbaker et al, 2003 ; Thomassen et al, 2014 ).…”
Section: Peritoneal Metastasis Of Gastric Cancermentioning
confidence: 99%